Therapeutic hypothermia in ST elevation myocardial infarction (STEMI): a long way to go - Liberale, Luca; Montecucco, Fabrizio (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Post-ischemic reperfusion injury is mediated by infiltration and activation of circulating inflammatory cell subsets (i.e., neutrophils) that early entered the area-at-risk and release proteases and reactive oxygen species (ROS) (1-3). A recent study demonstrated that during recovery neutrophil infiltration might be protective, thus favoring a proper scar formation and potentially preventing negative left ventricle remodeling (4). Given this pathophysiological complexity, some selective drugs targeting these cells failed to induce a clear benefit on mortality and post-ischemic heart failure development in experimental models (2,5).